FAKTOR-FAKTOR YANG BERHUBUNGAN DENGAN ASMA BRONCIAL PADA ANAK DI RUANG SAKURA RUMAH SAKIT PTPN II BANGKATAN BINJAI TAHUN 2017 - Sri Wahyuni (Akademi Keperawatan Kesdam I/Bukit Barisan Medan, 2017)
Broncial asthma is a chronic disease that is often found in children and adults in developing and developed countries. Since the last two decades, it has been reported that the total prevalence of bronchial asthma in the world is estimated to be 7.2% (6% in adults and 10% in children). The prevalence varies greatly by country and even differences are also found between regions within a country. The prevalence of bronchial asthma in various countries is difficult to compare, it is not clear whether the difference in numbers arises because of differences in diagnostic criteria or because there really are differences. This study is descriptive to determine the factors associated with bronchial asthma in children in the Sakura room of PTPN II Bangkat Binjai Hospital in 2017. Data collection in this study using questionnaires grouped based on allergies, cigarette smoke, sports, and air pollution from research results This shows that from 20 respondents (100%) it was known that 5 people (25%) were due to allergic factors, 5 people (25%) because of cigarette smoke, 4 people (20%) because of sports and 6 people (30%) due to air pollution . It is expected that the Rumah Akit will always increase counseling to patients about bronchial asthma in children.Keywords: broncial asthma factors